Highly Converged Valence Bands and Ultralow Lattice Thermal Conductivity for High‐Performance SnTe Thermoelectrics - Sarkar, Debattam; Ghosh, Tanmoy; Banik, Ananya; Roychowdhury, Subhajit; Sanyal, Dirtha; Biswas, Kanishka (Angewandte Chemie International Edition, 2020)
A two‐step optimization strategy is used to improve the thermoelectric performance of SnTe via modulating the electronic structure and phonon transport. The electrical transport of self‐compensated SnTe (that is, Sn1.03Te) was first optimized by Ag doping, which resulted in an optimized carrier concentration. Subsequently, Mn doping in Sn1.03−xAgxTe resulted in highly converged valence bands, which improved the Seebeck coefficient. The energy gap between the light and heavy hole bands, i.e. ΔEv decreases to 0.10 eV in Sn0.83Ag0.03Mn0.17Te compared to the value of 0.35 eV in pristine SnTe. As a result, a high power factor of ca. 24.8 μW cm−1 K−2 at 816 K in Sn0.83Ag0.03Mn0.17Te was attained. The lattice thermal conductivity of Sn0.83Ag0.03Mn0.17Te reached to an ultralow value (ca. 0.3 W m−1 K−1) at 865 K, owing to the formation of Ag7Te4 nanoprecipitates in SnTe matrix. A high thermoelectric figure of merit (z T≈1.45 at 865 K) was obtained in Sn0.83Ag0.03Mn0.17Te. The thermoelectric four: Highly converged valence bands and ultralow lattice thermal conductivity owing to nanoprecipitates lead to a high thermoelectric figure of merit (z T≈1.45 at 865 K) in Sn0.83Ag0.03Mn0.17Te, which is higher than that of Ag alone or Mn‐doped SnTe.